2008
DOI: 10.1242/jeb.016402
|View full text |Cite
|
Sign up to set email alerts
|

Computational mechanisms of mechanosensory processing in the cricket

Abstract: SUMMARY Crickets and many other orthopteran insects face the challenge of gathering sensory information from the environment from a set of multi-modal sensory organs and transforming these stimuli into patterns of neural activity that can encode behaviorally relevant stimuli. The cercal mechanosensory system transduces low frequency air movements near the animal's body and is involved in many behaviors including escape from predators, orientation with respect to gravity, flight steering, aggress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 72 publications
0
59
0
Order By: Relevance
“…2). Most cercal ascending interneurons have simple directional tuning curves with a single peak [1,10,19]. Further electrophysilogical experiments using intracellular recording and anatomical studies would reveal the details of the neuronal circuit that achieves complex processing, including direction-specific inhibition, in the VLNP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2). Most cercal ascending interneurons have simple directional tuning curves with a single peak [1,10,19]. Further electrophysilogical experiments using intracellular recording and anatomical studies would reveal the details of the neuronal circuit that achieves complex processing, including direction-specific inhibition, in the VLNP.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that stimulus direction is not represented topographically in the protocerebrum, unlike in the TAG [12,13,27]. More cells responded to air currents from the front than from behind; however, cercal sensory afferents and ascending interneurons including GIs have low sensitivity to stimuli directly in front of the animal [1,10,18]. As suggested by the reduction of the spike responses in the antennae-removed experiments, these cells could be activated by mechanosensory input from antennae stimulated by air currents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of the cerci of crickets and cockroaches, as well as the neural elements carrying and processing mechanosensory information have been extensively studied since the early 70s. Since then the cercal sensory system has become a classical model in neuro-ethology of sensory integration and behavioural guidance (Jacobs et al, 2008;Ritzmann, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on these insects focused on the neural basis of wind-detection (Bacon and Murphey, 1984;Jacobs and Miller, 1985;Jacobs andTheunissen, 1996, 2000;Jacobs et al, 1986Jacobs et al, , 2008Miller and Jacobs, 1984;Miller et al, 1991;Murphey, 1981;Paydar et al, 1999;Yono and Shimozawa, 2008), on the escape behaviour (Gras and Hö rner, 1992;Kanou et al, 1999Kanou et al, , 2006Tauber and Camhi, 1995;Schrader, 2000), and on the plasticity and recovery after cercal ablation (Kanou and Kondoh, 2004;Kanou et al, 1999Kanou et al, , 2001Kanou et al, , 2002. To stimulate the cerci, most studies employed air-puffs directed towards them.…”
Section: Introductionmentioning
confidence: 99%